2015
DOI: 10.1159/000369681
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam Inhibits the Apoptosis of Astrocytes Induced by Oxygen Glucose Deprivation via Targeting JAK2-STAT3 Signaling Pathway

Abstract: Background: There is an increasing interest in the role of astrocytes contributing to the intrinsic bioremediation of ischemic brain injury. The purpose of this study was to disclose the effects and mechanism of midazolam (MDZ) on the proliferation and apoptosis of astrocytes under oxygen glucose deprivation (OGD) condition. Methods: The astrocytes were assigned randomly into four groups: control group, OGD group, OGD+MDZ group, and OGD+MDZ+IL-6 group. The astrocytes were treated with MDZ at dose of 10 μmol/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…As shown in several previous studies, the JAK2-STAT3 signalling pathway regulates apoptosis-related genes, such as c-Caspase, Bcl-2, Bcl-x, Bax and Caspase-3 43, 44 . Additionally, one of the primary mechanisms responsible for the behavioural impairments induced by exposure to chronic stress may be related to excessive apoptosis 45, 46 .…”
Section: Discussionmentioning
confidence: 56%
“…As shown in several previous studies, the JAK2-STAT3 signalling pathway regulates apoptosis-related genes, such as c-Caspase, Bcl-2, Bcl-x, Bax and Caspase-3 43, 44 . Additionally, one of the primary mechanisms responsible for the behavioural impairments induced by exposure to chronic stress may be related to excessive apoptosis 45, 46 .…”
Section: Discussionmentioning
confidence: 56%
“…Cell apoptosis was measured by flow cytometry analysis as described previously [22]. Treated cells were harvested and re-suspended in 2.5 ml phosphate buffered solution (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Study found that both CLA (conjugated linoleic acid)-isomers increased TNF and IL-6 mRNA in primary astrocyte cultures indicate that astrocytes may contribute to neuronal inflammation [23]. It also showed that IL-6 could attenuate cell proliferation and anti-apoptotic effects of MDZ in astrocytes [24]. Thus, in this experiment we used IL-17 to stimulate the astrocytes cultured in vitro and to investigate the relationship of several inflammatory cytokines and chemokines, including regulatory proteins, which might provide a theoretical basis for anti-inflammatory therapy of SCI in clinic.…”
Section: Discussionmentioning
confidence: 96%